Funcionalidad familiar y el embarazo adolescente de los estudiantes de Primer año de Bachillerato paralelo A, de la Unidad Educativa Paltas, cantón Paltas, 2020-2021. - Hurtado Pogo., Nataly Yuliza (2022)
2.1 Abstract The research work entitled: Family functionality and adolescent pregnancy of first-year high school students parallel A, from the Paltas Educational Unit, Canton Paltas, 2020-2021, had as a general objective to investigate the influence of family functionality on pregnancy. adolescent of first-year parallel high school students A. It was a study with a quantitative approach, descriptive type, non-experimental and cross-sectional design, using scientific, analytical, inductive-deductive, synthetic and statistical methods; the Family System Evaluation Questionnaire -CESF and the survey on adolescent pregnancy were applied to 38 students of the sample. Of the results obtained in relation to family functionality, evaluated in its 2 dimensions, 86.84% maintain good emotional bonding, compared to 71.05% who claim to have good flexibility; Likewise, in relation to adolescent pregnancy, it is evident that 84.2% are aware of the consequences of adolescent pregnancy, 81.6% take measures to prevent adolescent pregnancy, and 86.8% know the frequent risks to the health of an adolescent. pregnant teenager. It is concluded that the investigated sample manifests maintaining a good family functionality (emotional bonding and flexibility); they also have knowledge about teenage pregnancy; A psychoeducational proposal for the prevention of adolescent pregnancy is designed in a functional family life through the video forum in the form of workshops. Keywords: Family functionality, teenage pregnancy, pregnancy prevention